Pendidikan Moderasi Beragama: Integrasi Epistemologi Keislaman dalam Menyikapi Pluralitas Agama di Indonesia - Fahmi Khumaini; Hamam Burhanuddin; Rz. Ricky Satria Wiranata (STAI Terpadu Yogyakarta, 2023)
This research seeks to reveal a perspective initiative in responding to religious plurality in Indonesia with an integrated approach to Islamic epistemology so that a moderate understanding can be obtained that is neither extreme-left nor extreme-right. This research is based on cases of intolerance in Indonesia, such as the ban on Christian worship in Bangsal, Mojokerto, East Java (2020), the burning of churches in Singkil, Aceh (2015), and the ban on the establishment of Hindu places of worship in Bekasi (2019), which triggered a debate on Indonesian social media that led to hate speech between religious people. This research is a qualitative descriptive study with a phenomenological approach to these cases. This study will answer 1. Discourse on Religious moderation Education in Indonesia 2. The model of Islamic integrity epistemology in responding to religious plurality in Indonesia 3. Implications of the integration of Islamic epistemology on pluralism. This research shows that the phenomenon of intolerance is a form of narrow religious perspective, so that a broader conception of religious perspective and approach is needed to realize a more harmonious Indonesian society Kata Kunci: Pendidikan Moderasi Beragama, Epistemologi Keislaman, Pluralitas Agama. Abstract: This research seeks to reveal a perspective initiative in responding to religious plurality in Indonesia with an integrated approach to Islamic epistemology so that a moderate understanding can be obtained that is neither extreme-left nor extreme-right. This research is based on cases of intolerance in Indonesia, such as the ban on Christian worship in Bangsal, Mojokerto, East Java (2020), the burning of churches in Singkil, Aceh (2015), and the ban on the establishment of Hindu places of worship in Bekasi (2019), which triggered a debate on Indonesian social media that led to hate speech between religious people. This research is a qualitative descriptive study with a phenomenological approach to these cases. This study will answer 1. Discourse on Religious moderation Education in Indonesia 2. The model of Islamic integrity epistemology in responding to religious plurality in Indonesia 3. Implications of the integration of Islamic epistemology on pluralism. This research shows that the phenomenon of intolerance is a form of narrow religious perspective, so that a broader conception of religious perspective and approach is needed to realize a more harmonious Indonesian society. Keywords: Religious Moderation Education, Islamic Epistemology, Plurality.